Stripped of Rights: The Battle for Justice and Legal Certainty for Stateless Persons in Indonesia - Muhammad, Muhammad (Indonesian Journal of Advocacy and Legal Services, 2024)
This research critically examines the justice system and legal certainty pertaining to stateless persons in Indonesia. Stateless individuals in Indonesia frequently encounter systemic discrimination and endure hardships due to inadequate legal protections. The study employs a normative juridical research approach, combining statutory analysis and conceptual exploration to assess the current regulatory framework. The findings underscore significant gaps in existing regulations that fail to adequately safeguard the rights of stateless persons. These individuals often struggle to access basic human rights such as education, healthcare, and employment, highlighting a critical need for legislative reforms. Legal certainty is a pivotal issue, as the ambiguity and inconsistencies within Indonesian laws contribute to the vulnerability of stateless populations. Furthermore, the research identifies discrepancies between national laws and constitutional mandates, which further complicate the legal landscape for stateless persons. This analysis aims to advocate for policy reforms that align with principles of justice and constitutional integrity, proposing measures to enhance legal protections and ensure equitable treatment for stateless individuals in Indonesia. By illuminating these challenges and proposing potential avenues for legal reform, this research seeks to contribute to broader discussions on human rights, migration, and legal justice within the Indonesian context, ultimately advocating for a more inclusive and just society for stateless persons